Analisis Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) di Lingkungan PT. X Tahun 2025 - Halisa Kurniati; Rachel Amanda Indaryati; Fransiscus A.C.Wakumoan (Jurnal Rumpun Ilmu Kesehatan, 2026)
The Occupational Health and Safety Management System (SMK3) is a crucial element in ensuring a safe and healthy work environment, particularly at PT X, where workers face high health and safety risks. Regulatory compliance, employee training, risk management, and management support are key factors in the successful implementation of SMK3. The use of adequate technology and infrastructure also supports the system's effectiveness. Furthermore, a strong safety culture and periodic evaluations contribute significantly to improving workplace safety. This study aims to adopt a comprehensive approach and provide ongoing support for SMK3 implementation at PT X. A cross-sectional method employing both qualitative and quantitative research designs was used. The sample consists of 164 respondents at PT X. The study results indicate the following: 1) Project commitments and policies were established directly based on company standards. 2) OHS planning for PT X construction projects involved hazard identification, risk assessment, and the determination of risk controls; this planning began with the creation of a safety plan based on initial assessments as well as relevant OHS laws and requirements. 3) Regarding implementation, workers and new employees received safety inductions and health checks. Personal Protective Equipment (PPE) was fully provided according to potential risks, and workers were required to use it while working in the field; routine SHE talks and toolbox meetings were conducted to facilitate OHS communication among workers. 4) OHS monitoring and evaluation involved periodic inspections to identify potential hazards arising from workplace conditions, equipment, materials, and worker actions; this process facilitated necessary corrective and preventive measures and ensured the provision of emergency equipment including emergency warning systems that were regularly inspected, tested, and maintained in accordance with regulations. 5) Review and improvement were carried out by compiling accident risk statistics and audit findings from the project, followed by addressing any identified deviations. Statistical analysis showed significant overall results (p ≤ 0.05), indicating a relationship between OHS implementation specifically regarding knowledge, attitude, training, and promotion and the occurrence of workplace accidents. The analysis results indicate that the variable most dominantly associated with the occurrence of workplace accidents is worker attitude, with an OR of 22.392; this means that workers with a negative attitude are 22 times more likely to experience a workplace accident compared to those with a positive attitude (95% CI: 4.091–122.559).